Hubungan Pengetahuan Dan sikap Masyarakat Dengan Keikutsertaan Vaksinasi COVID - 19 Di Dusun Surau Munai Kecamatan Rambah Hilir Kabupaten Rokan Hulu - Andria; Safitri, Nur; Aldriana, Nana; Wulandari, Sri (Maternity and Neonatal : Jurnal Kebidanan, 2022)
COVID 19 (Coronavirus Disease 2019) is a large group of viruses that can cause illness with mild to severe symptoms. The government's strategy to reduce the death rate from COVID 19 is by being vaccinated. The purpose of this study was to determine the relationship between community knowledge and attitudes with participation in COVID-19 vaccination. This type of research is quantitative analytic with Cross Sectinal design, data analysis using chi square test. The sample in this study was 154 respondents, who were selected by simple random sampling technique. Data were collected through direct questionnaires and google forms. The results of the unvariate analysis based on the level of the majority (114 people /74%) of the community have less knowledge while having good knowledge (40 people/26%). Based on the attitude of the majority of the community (90 people/(58.4)) being positive while being positive (90 people/58.4%) Furthermore, based on the participation of respondents who took part 122 (79.2%) and respondents who did not follow 32 (20 The results of the bivariate analysis showed that there was no relationship between public knowledge and participation in the vaccine with a p-value of 0.069 (>0.05), while for attitudes there was a relationship between attitudes and participation, a p-value of 0.001 (<0.05) towards the COVID 19 vaccine. Suggestions for the Surau Munai Village Government to collaborate with the health team to provide counseling about the COVID 19 vaccine to find out what vaccines are, the goals and benefits of vaccines, by conducting counseling.